Power Rotation and Crisis of Political Succession in Nigeria - Agudiegwu, Moses Ogbonna; Ngwu, Elias Chukwuemeka; Amulu, Sampson Obum (University of Nigeria Journal of Political Economy, 2021)
The quest for a political system that will guarantee stability and national development and serve as a panacea to Nigeria’s political succession crisis has remained elusive. This study seeks to find a political framework that constitutionally shares power among the diverse regional and ethnic groupings and promote mutual trust and national integration in Nigeria. Empirical evidence was applied in the discussion to interrogate the thesis that the non-entrenchment of the rotation of power in the constitution encourages political succession crisis. The study used documentary method for data collection from secondary sources, and applied content analysis for data analysis. Among the key findings of the study were that the absence of constitutional provision for rotation of power encourages crisis of political succession and undermines national development. It therefore recommends that there is urgent need for constitutional provision for rotation of power to all the six geo-political zones in Nigeria in order to assuage the fears of domination and marginalization, reduce the hostile contest for power among the component units and ensure national development.